2019
DOI: 10.1021/acs.langmuir.9b00194
|View full text |Cite
|
Sign up to set email alerts
|

Size-Controlled Preparation of Microsized Perfluorocarbon Emulsions as Oxygen Carriers via the Shirasu Porous Glass Membrane Emulsification Technique

Abstract: We have developed microsized perfluorocarbon (PFC) emulsions with different sizes as artificial oxygen carriers (OCs) via Shirasu porous glass membrane emulsification. Monodispersed PFC emulsions with narrow size distribution were obtained. By changing the membrane pore size, we were able to precisely control the size of emulsions and fabricate emulsions similar in size to human red blood cells. Behaviors of Pluronics with different physiochemical properties (F127, F68, P85, and P103) as surfactants were also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…By using different membrane pore diameters, we controlled the size of the DFCs in the size range of these circulating blood cells. In addition to previous research [24,25] including ours, [16,26] the size of emulsions and pore size showed a proportional relationship. Based on this size control of DFCs, precise shell thickness control was achieved (Figure S4, Supporting Information).…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…By using different membrane pore diameters, we controlled the size of the DFCs in the size range of these circulating blood cells. In addition to previous research [24,25] including ours, [16,26] the size of emulsions and pore size showed a proportional relationship. Based on this size control of DFCs, precise shell thickness control was achieved (Figure S4, Supporting Information).…”
Section: Discussionsupporting
confidence: 58%
“…[26] The desirable size was similar to that of the hRBCs. Size control was achieved via the homogeneous pore size distribution of SPG membranes [16,[24][25][26] (Figure S2, Supporting Information). By using different membrane pore diameters, we controlled the size of the DFCs in the size range of these circulating blood cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…O 2 molecules were dissolved in PFCs by a weak intermolecular van der Waals force, and the O 2 loading or release was passively decided by the O 2 partial pressures in certain physiological environments. , Although the PFC maintains a high O 2 solubility, its O 2 release efficiency is low due to the diffusion pattern associated with the O 2 concentration gradient. Besides, the clinical application of PFC has also been limited by its poor solubility in water and rapid metabolism. , To circumvent these problems, a variety of nanoperfluorocarbons (nano-PFCs) have been established by formulating PFCs into nanocarriers. In these nano-PFCs, O 2 could be timely released in response to external stimulus such as acidic pH or laser irradiation.…”
Section: Nanoenabled O2-carrying Tacticsmentioning
confidence: 99%